2017
DOI: 10.1002/lary.26960
|View full text |Cite
|
Sign up to set email alerts
|

National trends in otolaryngology intern curricula following Accreditation Council for Graduate Medical Education changes

Abstract: NA Laryngoscope, 1811-1816, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…As with most surveys, this study was not without limitations. The recorded response rate was 32%, which limits generalization of reported findings and potential implications; however, this is in line with the typical response rate for program director surveys of this type . Our results may also not reflect the overall education and practice patterns of C1‐INH‐HAE among residency programs nationwide.…”
Section: Discussionmentioning
confidence: 44%
“…As with most surveys, this study was not without limitations. The recorded response rate was 32%, which limits generalization of reported findings and potential implications; however, this is in line with the typical response rate for program director surveys of this type . Our results may also not reflect the overall education and practice patterns of C1‐INH‐HAE among residency programs nationwide.…”
Section: Discussionmentioning
confidence: 44%
“…The ACGME outlines specific competency requirements for graduating residents, and in 2016 modified the clinical experience of postgraduate year (PGY)-1 residents to include 6 months of otolaryngology instead of the previous 1 month. 7 However, this cannot explain the increase in overall case numbers prior to 2016.…”
Section: Discussionmentioning
confidence: 97%
“…Our group previously performed a national survey study investigating how programs are adapting intern curriculum, particularly in response to changing ACGME requirements. 2 With the additional time on service, the most common trends included additional experiences on general ORL-HNS and H&N oncology rotations, in addition to a greater number of experiences on other ORL-HNS subspecialty services. Additionally, we found that there was an overall increase in exposure to additional educational opportunities, including procedural simulation, boot camp curricula, resident didactics, and various educational conferences.…”
Section: Discussionmentioning
confidence: 99%
“…1 With this significant change in available ORL-HNS training time, our group noted great variation in the ways individual ORL-HNS programs across the country are choosing to address the ACGME changes in curriculum requirements. 2 With this knowledge, our group identified an opportunity to develop a novel PGY-1 rotation integrating simulation-based otolaryngology and anesthesiology training with a structured interdisciplinary didactic curriculum.…”
Section: Introductionmentioning
confidence: 99%